Potential Mobility of Heavy Metal in Soil Using Electrochemical Method - Siti Khadijah, Che Osmi; Siti Fatimah, Che Osmi; Ezahtul Shahreen, Ab Wahab (Penerbit UMP, 2011)
This paper investigates the potential mobility of heavy metal in soil using an electrochemical method in hoped to be used as an extraction technique to reduce the number of soil contaminated sites. In this study, the mobility of chromium (Cr) in the fully saturated soil sample with 1000ppm concentration was investigated by checking the changes of pH performance. A total of four different tests were conducted, and each of the tests is divided equally into two sample preparation. Sample preparation 1 and 2 were applied with electric field strength of 5 V/cm and 10 V/cm respectively, which achieved from a DC power supply. The total duration of tests is six hours and the result was taken and This paper investigates the potential mobility of heavy metal in soil using an electrochemical method in hoped to be used as an extraction technique to reduce the number of soil contaminated sites. In this study, the mobility of chromium (Cr) in the fully saturated soil sample with 1000ppm concentration was investigated by checking the changes of pH performance. A total of four different tests were conducted, and each of the tests is divided equally into two sample preparation. Sample preparation 1 and 2 were applied with electric field strength of 5 V/cm and 10 V/cm respectively, which achieved from a DC power supply. The total duration of tests is six hours and the result was taken and recorded at every one hour. Consequently, the pH value of the soil significantly affects the mobility of heavy metal ions. The mobility of chromium (III) from the soil using the electrochemical method was achieved by considering changes of pH values during experimental works. The pH values are slightly increased at the initial experiment, but then start to decrease after four hours for sample preparation 1 and after three hours for sample preparation 2. In addition, the results also showed that the increased experimental time might induce a higher mobility of chromium in soil due to the changes in pH value performance. recorded at every one hour. Consequently, the pH value of the soil significantly affects the mobility of heavy metal ions. The mobility of chromium (III) from the soil using the electrochemical method was achieved by considering changes of pH values during experimental works. The pH values are slightly increased at the initial experiment, but then start to decrease after four hours for sample preparation 1 and after three hours for sample preparation 2. In addition, the results also showed that the increased experimental time might induce a higher mobility of chromium in soil due to the changes in pH value performance.